Konvensi konvensi wina. Tentang hubungan diplomatik, hubungan konsuler dan hukum perjanjian/traktat - WASITO (Andi Offset, 1984)
Konvensi konvensi wina. Tentang hubungan diplomatik, hubungan konsuler dan hukum ...